INTERDISCURSIVE RELATIONS AND METAFORRIC EFFECTS IN THE JOURNALISTIC GENRE - Andrade Barroso Peixoto, Priscila; Charla Ferreira Tinoco, Dhienes; Crispim França Luquetti, Eliana (LINKSCIENCEPLACE, 2026)
This article presents a reflection on the work with interdiscursive elements in the classroom through the journalistic genre. It starts from the idea of text as a linguistic-historical object that performs the discursiveness that constitutes it. Thus, it is believed that the relationship between discourse and historical context is inseparable. Moreover, according to the assumptions of the discourse analysis, the journalistic genre is constituted as the form of interdiscursive networks. Thus, the objective is to understand how interdiscursivity affects the effects of meaning and how the specificities of journalistic work aid in the analysis of the relations and effects that discursive practice demonstrates in the elaboration and understanding of the text.